Inovações sociais e governança regional no Quebec: que lugar resta aos novos movimentos sociais? - Denyse Côté; Étienne Simard (Ciências Sociais Unisinos)
Social movements have been important sources of change and social innovation in Québec, at the national level but also in each of its regions where they were imbedded. Grassroots social movements were the building blocks of what is now known as the ¿Québec model¿ of governance. This paper discusses whether a new generation of social movements could emerge in the Québec regions where new co-construction mechanisms for policies and programs have been integrated into regional governance structures. How does this new generation of social activists position itself in regard to these new policies and structures inherited from half a century of social movements led by their predecessors? The article will focus on structures and mechanisms of concertation of regional authorities with local/regional community groups. It is based on data collected in various research projects in seven Québec regions and on longstanding professional experiences and experiences in advocacy. A parallel will be drawn between the concept of social innovation inherent to social movements and the one adopted by regional authorities based upon Schumpeter¿s economical analysis.